Individualus konstitucinis skundas ir „Romuvos“ byla - Kūris, Egidijus; Pūraitė-Andrikienė, Dovilė (Vilnius University Open Series, 2024)
The article deals with the legal basis for and the procedure of granting the status of State-recognised religious association to religious communities in Lithuania. It is based on the case study of the negative experience of the Ancient Baltic religious association Romuva, which was not granted, by the Parliament, the said status. Subsequently, the association won its case in the European Court of Human Rights (8 June 2021), the Lithuanian Constitutional Court adopted the ruling (7 September 2021), whereby it approved as constitutional the legislation on which the association’s request to be granted this status was based, and the relevant statute was amended to ensure greater transparency of the granting procedure. Despite that, the Parliament repeatedly refused to grant the said status to the association involved. The article explores in great detail the parliamentary debate during the examination of both the first and the second requests. The authors explore the possibilities for the association to pursue further litigation in the Lithuanian courts, including making use of the individual constitutional complaint to the Constitutional Court, the new measure introduced in the Lithuanian legislation only in 2019. It is demonstrated that the case-law of the Constitutional Court itself (of 2010, as well as post-2019) prevents the association from making effective use of that measure, thus leaving it with no other alternative than lodging a new application to the European Court of Human Rights, which then would have to decide on whether, in the cases like this, an individual constitutional complaint is to be considered an effective measure within the meaning of Article 35 of the European Convention on Human Rights which has to be exhausted at the domestic level.
Keywords: individualus konstitucinis skundas; Europos Žmogaus Teisių Teismas; valstybės pripažinimo suteikimas religinėms organizacijoms; Konstitucinis Teismas